Dilema Nilai Islam dan Kebutuhan Pasar Kerja:: Perspektif Mahasiswa Tentang Kurikulum PTKI - Irawan; Rohmat Mulyana Sapdi; Adib Rofiuddin Basori (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2025)
Islamic Religious Higher Education (PTKI) faces the challenge of balancing the idealism of Islamic values with the pragmatic demands of the labor market. This research aims to explore students' perspectives on this dilemma within the PTKI curriculum. Using a mixed-methods approach, this study collected quantitative data through a survey of 99 students and qualitative data through in-depth interviews. The findings reveal a significant perception gap: a majority of students (41.4%) feel the curriculum is imbalanced and overly theoretical, with 54.6% considering it irrelevant to current job market needs. This critical view is significantly more pronounced among students with internship experience (62.5%) compared to those without (33.3%). Despite this, an overwhelming majority of students (96%) do not desire a dichotomy but rather support an integrated curriculum that explicitly combines Islamic values with professional skills. The study concludes that the current theory-centric curriculum model is inadequate. It is recommended that the PTKI curriculum be reconstructed towards an applicative hybrid model that integrates theory and practice, thereby producing graduates who are not only professionally competent but also possess strong moral integrity